Factor Structure, Internal Consistency, and Screening Sensitivity of the GARS-2 in a Developmental Disabilities Sample. (15th February 2016) - Volker, Martin A.; Dua, Elissa H.; Lopata, Christopher; Thomeer, Marcus L.; Toomey, Jennifer A.; Smerbeck, Audrey M.; Rodgers, Jonathan D.; Popkin, Joshua R.; Nelson, Andrew T.; Lee, Gloria K.
Abstract : The Gilliam Autism Rating Scale-Second Edition (GARS-2) is a widely used screening instrument that assists in the identification and diagnosis of autism. The purpose of this study was to examine the factor structure, internal consistency, and screening sensitivity of the GARS-2 using ratings from special education teaching staff for a sample of 240 individuals with autism or other significant developmental disabilities. Exploratory factor analysis yielded a correlated three-factor solution similar to that found in 2005 by Lecavalier for the original GARS. Though the three factors appeared to be reasonably consistent with the intended constructs of the three GARS-2 subscales, the analysis indicated that more than a third of the GARS-2 items were assigned to the wrong subscale. Internal consistency estimates met or exceeded standards for screening and were generally higher than those in previous studies. Screening sensitivity was .65 and specificity was .81 for the Autism Index using a cut score of 85. Based on these findings, recommendations are made for instrument revision.